Massive pleural effusions in cryptococcal meningitis. - Wong, C.M.; Lim, K.H.; Liam, C.K. (1999)
Cryptococcal infection uncommonly presents with pulmonary manifestations and even more rarely so as massive bilateral effusions. Pleural involvement is usually associated with underlying pulmonary parenchymal lesions and is unusual while on antifungal therapy. We report a patient with cryptococcal meningitis who, while on intravenous 5-flucytosine and amphotericin B, developed life-threatening bilateral massive pleural effusions with evidence of spontaneous resolution, consistent with prior hypothesis of antigenic stimulation as the cause of pleural involvement.